EFEKTIVITAS ANTIBAKTERI Aglaophenia cupressina Lamoureoux TERHADAP BAKTERI PATOGEN - Ari Tjahyadi; Rosdarni Rosdarni (BIOMA : JURNAL BIOLOGI MAKASSAR, 2021)
The level of resistance possessed by most antibiotics is a major problem that must be treated immediately. Several studies on the study of antibiotic resistance have suggested that studies be carried out to find new antimicrobials. One of the antimicrobials that have the potential to inhibit and even have bacteriocidal properties against several resistant pathogens is Aglaophenia cupressina Lamoureoux from the sea. This species has long been used by the people of Linsowu village as a natural anti-toxic agent. This study aims to determine the effect of the concentration of Hydrozoid extract on the growth of pathogenic bacteria that cause infection. This research is an experimental study with a post test only continue design. The research method was carried out in 3 stages, namely the stage of making sample separation in the form of extraction, the stage of testing the extract against 3 different bacteria namely E.coli, Staphylococcus aureus and Streptococcus mutans and measuring the inhibition zone compared to cloranphenicol. The results showed that the extract of Aglaophenia cupressina L. increased the growth of E. coli compared to the two tested bacteria with a zone of 7 mm inhibition based on the level of effectiveness, the extract of Aglaophenia cupressina Lamoureoux is bacteriostatic against E. coli